Incidence and Associated Factors of Occupational Contact Dermatitis in Wood Furniture Finishing Workers - Belinda Faustinawati; Diah Adriani Malik; Liza Afriliana (Diponegoro International Medical Journal, 2025)
Background: Occupational contact dermatitis (OCD) is a prevalent skin disease caused by workplace exposure to exogenous agents. Wood furniture finishing workers are at high risk due to significant contact with allergens and irritants, yet specific research on this group remains limited.Objective: To determine the incidence rate of OCD and analyze its associated factors among wood furniture finishing workers.Methods: An observational analytical study with a cross-sectional design was conducted involving 36 wood furniture finishing workers. Data on potential risk factors were collected using a modified Nordic Occupational Skin Questionnaire (NOSQ)-2002. The diagnosis of OCD was established using the Mathias criteria. A patch test was performed with four common industrial allergens (Formaldehyde 1%, Isothiazolinone 0.2%, Cobalt Chloride 1%, and Colophony 20%) to identify specific sensitisations. Data were analyzed using Mann-Whitney, Fisher's exact, and logistic regression tests.Results: The incidence rate of OCD was 58.3% (21 of 36 subjects). Positive patch test results were found in 20 subjects (55.5%), with Cobalt Chloride 1% being the most frequent sensitizer (44.4%), followed by Colophony 20% (30.5%), Formaldehyde 1% (19.4%), and Isothiazolinone 0.2% (13.8%). Univariate analysis identified younger age (p=0.012), shorter length of work (p=0.001), and a history of atopic dermatitis (p<0.001) as significant risk factors. Multivariate logistic regression analysis confirmed that younger age was the strongest predictor for OCD (OR 1.086; 95% CI 1.018–1.158; p=0.012).Conclusion: Wood furniture finishing workers exhibit a high incidence of OCD. Younger age, shorter work duration, and a history of atopic dermatitis are significant associated factors. These findings highlight the need for targeted preventive strategies, including worker education and improved safety measures in the furniture finishing industry.